Wushu: a culture of adversaries. Issue 3 (2nd September 2019) - Dai, Guo-Bin; Lu, An
ABSTRACT: Wushu is widely misunderstood and its essentially combative nature is being challenged in public discussion. Understanding and recovering its essential nature has become a core issue. This paper first conducts a review of the history of the Chinese hieroglyphic 武 ( Wu ) which is the core of the phrase of Wushu, and explores the word's two most widely-accepted interpretations: 'to carry a dagger-axe to fight with' and 'to put away the dagger-axe and stop fighting'. Understanding these two interpretations of Wu is the key to understand Wushu which is an art about Wu . Second, this paper, referencing cultural history, analyzes different methods of Wushu practice: Gedou (free combat), Taolu (compiled routine) and Gongfa (basic prowess). Third, based on Wittgenstein's concept of family resemblance, this paper analyzes the different sorts of opponents, either real or imagined, in Taolu, Gedou, and Gongfa . Finally, this paper redefines Wushu as a culture of adversaries where such adversaries implicitly transfer the practitioner's focus 'from non-human to human' and 'from others to the self'.